2022
DOI: 10.1039/d2tb00027j
|View full text |Cite
|
Sign up to set email alerts
|

Facile preparation of a thermosensitive and antibiofouling physically crosslinked hydrogel/powder for wound healing

Abstract: To improve the therapeutic effect of hydrogel for damaged tissue, a series of hydroxybutyl chitosan (HBC) and poly (sulfobetaine methacrylate) (PSBMA) composite hydrogels (HBC-PSB) with thermosensitivity, self-healing, antibiofouling, and synergistic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 43 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…CS-based thermosensitive gels have been widely studied as drug delivery materials and used in wound healing, anti-tumor, nasal delivery, and other applications. [54][55][56] Here we selected CS as the material to prepare temperature-sensitive CS/CSCPs/β-GP gel to enhance its local treatment effect after dermal application. The CS/ CSCPs/β-GP gel had a phase transition temperature of 36.3 °C, which is similar to body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…CS-based thermosensitive gels have been widely studied as drug delivery materials and used in wound healing, anti-tumor, nasal delivery, and other applications. [54][55][56] Here we selected CS as the material to prepare temperature-sensitive CS/CSCPs/β-GP gel to enhance its local treatment effect after dermal application. The CS/ CSCPs/β-GP gel had a phase transition temperature of 36.3 °C, which is similar to body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…HBC was synthesized was synthesized via an etherification reaction according to the previous reports and the relative details are given in Supporting Information. [ 35 ]…”
Section: Methodsmentioning
confidence: 99%
“…reported that zwitterionic hydrogels can promote tissue regeneration and recovery by transforming the macrophage type from M1 to M2. [ 32,33 ] Our previous work also showed that zwitterionic hydrogels have remarkable effects on peritoneal adhesion prevention, [ 34,35 ] which can inhibit initial and late‐stage development by impeding fibroblast and exudate adhesion. [ 36 ] Interestingly, an increasing number of studies have determined that epigallocatechin‐3 gallate (EGCG), which is an important component of tea polyphenols, exhibits excellent antioxidative, anti‐inflammatory, antibacterial, and immunoregulatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…The construction of polyelectrolyte contains cationic polymers, anionic polymers, [29] and zwitterionic polymers. [11,30,31] Due to the large amounts of ionic groups inside, it can tightly attach to the substrates through electrostatic interactions, dipole interactions, and hydrogen bonds. Gao and co-workers [32] reported a polyzwitterion-clay nanocomposite hydrogel which has excellent self-healing property and reversible skin adhesiveness due to the zwitterionic groups.…”
Section: Introductionmentioning
confidence: 99%
“…And it could exhibit excellent biocompatibility, as our previous studies showed that the PSBMA-based hydrogel has been widely used in the biomedical field. [31,36,37] In addition, the different forms of adhesive would also be suitable for different application conditions.…”
Section: Introductionmentioning
confidence: 99%